Diet and foraging behaviour of the brown hyaena (hyaena brunnea, Thunberg, 1820) in the southern Kalahari - Bothma, Jacobus du P. (University of Pretoria, 2024)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 1977.